2021
DOI: 10.1002/advs.202102587
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nanomaterials with Intrinsic Singlet Oxygen Generation for Photodynamic Therapy

Abstract: Inorganic nanomaterials with intrinsic singlet oxygen (1O2) generation capacity, are emerged yet dynamically developing materials as nano‐photosensitizers (NPSs) for photodynamic therapy (PDT). Compared to previously reported nanomaterials that have been used as either carriers to load organic PSs or energy donors to excite the attached organic PSs through a Foster resonance energy transfer process, these NPSs possess intrinsic 1O2 generation capacity with extremely high 1O2 quantum yield (e.g., 1.56, 1.3, 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 217 publications
0
40
0
Order By: Relevance
“…Au NPs have surface plasmon resonance (SPR), chemical inertness and excellent biocompatibility, which are mainly used as passivation agents, drug delivery agents, imaging agents, and photothermal agents, which have different characteristic shapes, such as particles, rod-shaped, cluster-shaped, shell-shaped, spike-shaped and star, etc., ( Younis et al, 2021 ). In PDT, gold nanoparticles can be used alone or as part of a multifunctional nanomaterial hybrid system for PSs delivery.…”
Section: Strategies For Nanoparticle-based Photocontrolled Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Au NPs have surface plasmon resonance (SPR), chemical inertness and excellent biocompatibility, which are mainly used as passivation agents, drug delivery agents, imaging agents, and photothermal agents, which have different characteristic shapes, such as particles, rod-shaped, cluster-shaped, shell-shaped, spike-shaped and star, etc., ( Younis et al, 2021 ). In PDT, gold nanoparticles can be used alone or as part of a multifunctional nanomaterial hybrid system for PSs delivery.…”
Section: Strategies For Nanoparticle-based Photocontrolled Deliverymentioning
confidence: 99%
“…Ag NPs have higher 1 O 2 yield than Au NPs and Pt NPs due to stronger SPR ( Younis et al, 2021 ). Inspired by the ability of ICD to transform tumors from cold to heat by inducing tumor cells to release tumor antigens and damage-associated molecular patterns (DAMPs) and then enhance T cell proliferation and infiltration ( Xu et al, 2022 ).…”
Section: Strategies For Nanoparticle-based Photocontrolled Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are active research in progress in the field of nanotechnology in developing PSs with greater tumor selectivity, enhanced hydrophilicity, and strong photosensitivity to yield a reliable photodynamic reaction. The studies show that metal nanoparticles such as gold, silver and copper, manganese, aluminum nanoparticles; organic–inorganic hybrid nanoparticles, metal oxide nanoparticles, metal sulfide nanoparticles, Cd-free nanostructured metal chalcogenides (NMCs) have been extensively investigated in PDT [ 22 25 ]. While nanoparticles surface endows increased chemical activity, they require relatively low-power radiation to lead photo-stimulated reaction to generate singlet oxygen [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nanophotosensitizers, which are photosensitizer-incorporated nano-sized carriers, have been suggested as an ideal candidate for PDT [ 12 , 13 , 14 ]. Various biocompatible polymers or nanomaterials such as natural polysaccharides, dendrimers, iron oxide nanoparticles and synthetic polymers have been investigated to fabricate nanophotosensitizers [ 12 , 13 , 14 , 15 , 16 ]. Chin et al reported that poly(vinylpyrrolidone) (PVP)-Ce6 formulations accelerate the tumor accumulation of photosensitizers and show fast clearance from the skin of nude mice [ 11 ].…”
Section: Introductionmentioning
confidence: 99%